2015
DOI: 10.1039/c4gc00919c
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of a bottom-up hydrolytic synthesis of TiO2 nanoparticles

Abstract: A green metrics evaluation of the bottom-up hydrolytic sol–gel synthesis of titanium dioxide (TiO2) nanoparticles has been performed by following two different approaches, namely, EATOS software and LCA methodology. Indeed, the importance of engineered nanomaterials is increasing worldwide in many high-technological applications. Due to the as yet completely un-established environment and human health impact of nano-sized materials, the possibility of at least choosing a greener synthetic strategy through an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…While this route proved to be to some extent effective, the use of metal halides and highly corrosive acid catalysts raises questions concerning the protocol safety and its sustainability. 15 Moreover, residual halides -strongly adsorbed to the material surface-have additional drawbacks in electronic and biomedical applications with undesirable effects, pitfalls and misleading results. The simultaneous engineering of the crystallinity and mesoporosity, which is another challenging issue in the chemistry of metal oxides compared to silicates, has been attempted by several approaches.…”
Section: Introductionmentioning
confidence: 99%
“…While this route proved to be to some extent effective, the use of metal halides and highly corrosive acid catalysts raises questions concerning the protocol safety and its sustainability. 15 Moreover, residual halides -strongly adsorbed to the material surface-have additional drawbacks in electronic and biomedical applications with undesirable effects, pitfalls and misleading results. The simultaneous engineering of the crystallinity and mesoporosity, which is another challenging issue in the chemistry of metal oxides compared to silicates, has been attempted by several approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SHYMAN process, there is no NP release to the air, there is only negligible release of NPs during cleaning procedures and waste water treatment as it is described in literature 18 . As for NPs release during the use stage, Som et al 19 states that the initial results from Vorbau et al 20 , on the abrasion of products incorporating nanomaterial, such as coatings incorporating ZnO, show that no significant release of nanoparticles were detected and that the NPs were still embedded in larger particles.…”
Section: Data Collectionmentioning
confidence: 99%
“…A number of methods are available to produce thin films: i) dip coating, ii) spin coating, iii) spray coating, iv) roller coating, and v) electro-phoretic deposition. Recently, Ferrari and his group [31] have reported new results in order to optimize the sol-gel synthesis of TiO 2 at the industrial scale; their results showed that TiO 2 , produced by the sol-gel using titanium tetraisopropoxide as the precursor, presented a high environmental impact and cost due to the energy used to prepare this precursor. This problem can be resolved by reducing the non-renewable energy consumption, using microwave technique to heating the reaction mixture due to the more efficient heat transfer mechanism, using renewable energy, as solar cells or substituting titanium tetraisopropoxide by other TiO 2 precursors.…”
Section: Advanced Technique: Sol-gel and Aerosolmentioning
confidence: 99%